A simple and efficient method for cryopreservation and recovery of viable Plasmodium vivax and P. falciparum sporozoites. Issue 5 (October 2016) - Singh, Naresh; Barnes, Samantha J.; Jenwithisuk, Rachaneeporn; Sattabongkot, Jetsumon; Adams, John H.
Abstract: Plasmodium falciparum and Plasmodium vivax sporozoites are the crucial stages of malaria parasites that initiate infection in humans. However, studies to develop new vaccines and drugs targeting these infective stages remain insufficient due to limited availability of sporozoites for research. This is a consequence of relatively few facilities that are established to produce sporozoites of human malaria parasites, sporozoites remaining viable for only a few days, and infected mosquitoes being a biohazard, making them difficult to transport. Cryopreservation of sporozoites offers the potential to alleviate these limitations and enhance sporozoite availability. These experiments were performed to evaluate methods for cryopreservation of P. vivax and P. falciparum sporozoites. Sporozoites, isolated in sterile buffer from infected mosquitoes by manual dissection of salivary glands, were cryopreserved using several types of commercially available serum-free cryoprotective solutions. The efficiency of cryopreservation was validated by a standard in vitro gliding motility assay as a measure of sporozoite activity. Viability of infective sporozoites was defined as percent gliding of sporozoites attached to the coverslip. Significant differences were observed among the cryopreservation media and protocols evaluated, with CryoStor CS2 giving the best results for both P. falciparum and P. vivax, whereas Hestar 200 worked efficiently only for P. vivax sporozoites. Further improvement in recovery of viable sporozoites would be anticipated using automated controlled-rate freezing equipment. Our results demonstrate that cryopreservation provides an alternative for experimental studies that currently rely on fresh P. falciparum and P. vivax sporozoites. Graphical abstract: Highlights: Simple protocol cryopreserves Plasmodium sporozoites without need for specialized equipment. Cryostor CS2 effectively cryopreserves P. vivax and P. falciparum sporozoites. Hestar 200 effectively cryopreserves P. vivax sporozoites.